Treatment of Deep Infection after Total Hip Replacement - YOSHIDA, Kazuhisa (Japanese Journal of Rheumatism and Joint Surgery, 1989)
Nine hips of 8 cases with deeply infected total hip replacement (THR) were treated in our clinic and at a related hospital. There was early infection in 2 hips (one rheumatoid and one avascular necrosis), and late infection in 7 hips (all rheumatoid) . The infection rate in the total number of THRs (480 hips) in our clinic was 1.25%; 3.8% in rheumatoid patients and 0.3 % in osteoarthritis. The organisms involved were St. aureus in 4 hips, St. epidermidis in 3, St. f aecalis in one and serratia in one. Two hips (St. aureus, St. epidermidis) were cured with wide curettage and wire removal combined with continuous irrigation. Total removal of the THR system was carried out in 5 hips (4 cases) with irrigation. Two cases died due to sepsis after curettage. The other 6 cases were followed up at an average of 54 months, ranging from 8 to 130 months. No signs of infection were detected in any of them. Clinically, 3 patients (one curettagge and 2 prosthesis) were able to walk with crutches, another was ambulatory with a wheel chair, and the other 2 rheumatoid patients were bedridden. At present, no re-replacement surgery has been scheduled due to individuals' situations and unwillingness.